Hedonism Portrayed in Tony Kushner’s Play Script “Angels in America” - Aurelies Riani Mangetan; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2021)
This study aimed to discover and explained the hedonism of the main characters in Tony Kushner’s play script entitled “Angels in America”. The data sources used in this study was the play script of “Angels in America”. The writer used descriptive qualitative research method through Sociological approach. Data were obtained by using the techniques of reading, noting, and analyzing. While in classifying and analyzing the data, the writer used Weijer’s theory of Hedonism. The writer found 20 data of hedonism which were divided into 2 types of hedonism. The first type was hedonistic egoism with 10 data and the second type was value hedonism with also 10 data. The findings also included the factors that cause hedonism such like life style, personal problems, medicine, ego, and homosexualism then the impacts which were medicine addicted, aggression, being out of control, egoism and illness.